2001
DOI: 10.1208/ps030108
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent dissolving nano- and microparticles for improved peroral delivery of a highly lipophilic compound in dogs

Abstract: RR01, a new highly lipophilic drug showing extremely low water solubility and poor oral bioavailability, has been incorporated into pHdependent dissolving particles made of a poly(methacrylic acid-co-ethylacrylate) copolymer. The physicochemical properties of the particles were determined using laser-light-scattering techniques, scanning electron microscopy, highperformance liquid chromatography, and x-ray powder diffraction. Suspension of the free drug in a solution of hydroxypropylcellulose (reference formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Other pharmaceutical scientists have also stated that spray-dried particles developed a shriveled shape and led to high surface area, which is advantageous for dissolution enhancement, and that shrinking may also be due to quick drying in the spraying compartment 26,27. A shriveled shape might also be due to the lack of a plasticizer.…”
Section: Resultsmentioning
confidence: 99%
“…Other pharmaceutical scientists have also stated that spray-dried particles developed a shriveled shape and led to high surface area, which is advantageous for dissolution enhancement, and that shrinking may also be due to quick drying in the spraying compartment 26,27. A shriveled shape might also be due to the lack of a plasticizer.…”
Section: Resultsmentioning
confidence: 99%
“…In our experiment, we could not increase the concentration of the solid feed which, in turn, would increase the particle size; however, this is beyond the scope of our study. [53][54][55] Design…”
Section: Surface Morphologymentioning
confidence: 99%
“…To manipulate intestinal luminal pH, we chose a pH-dependent anionic polymer, Eudragit L100-55 (Figure 1), which is used commonly for enteric coating of oral formulations. 28 This polymer is not dissolved under acidic condition, and it becomes soluble and release protons under weakly acidic (pH 6) to alkaline condition due to its carboxyl groups, thereby controlling the intestinal luminal pH to be acidic. We confirmed that the pH of a buffer was decreased by the addition of Eudragit L100-55 in a concentration-dependent manner (Figure 2).…”
Section: Discussionmentioning
confidence: 99%